The lives of Brian : a memoir - Johnson, Brian, 1947 October 5- (Dey St., an imprint of William Morrow, 2022)
The lead singer of AC/DC relates his childhood in a working class town in England, starting his own band, and joining AC/DC to record the iconic "Back in Black" album, which would become the best-selling hard rock album in history.